2018
DOI: 10.1002/acp.3385
|View full text |Cite
|
Sign up to set email alerts
|

The effects of narrative practice on children's testimony and disclosure of secrets

Abstract: The present study explored the effects of different types of narrative practices on the accuracy and abundance of information elicited from children and the disclosure of secrets. Seventy-one children ages 3-6 years experienced a scripted encounter with a photographer; then they were interviewed about the event after participating in one of four different narrative practices. The narrative practices comprised either a discussion of topics drawing from episodic memory or topics drawing from semantic memory. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Contrary to our expectations, we did not see any significant differences between the two rapport conditions for the children’s disclosure rate, amount of information, accuracy rate, or type of detail. While unexpected, these findings concur with several past studies that have not found a significant difference between different verbal rapport building strategies (Hardy & Leeuwen, ; Lyon et al ., ; Yi & Lamb, ). Furthermore, these results contradict the findings by Collins () who did observe a difference in productivity with school‐aged children when using a jigsaw compared to a verbal rapport condition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Contrary to our expectations, we did not see any significant differences between the two rapport conditions for the children’s disclosure rate, amount of information, accuracy rate, or type of detail. While unexpected, these findings concur with several past studies that have not found a significant difference between different verbal rapport building strategies (Hardy & Leeuwen, ; Lyon et al ., ; Yi & Lamb, ). Furthermore, these results contradict the findings by Collins () who did observe a difference in productivity with school‐aged children when using a jigsaw compared to a verbal rapport condition.…”
Section: Discussionmentioning
confidence: 99%
“…The children’s accounts were quantified into information units using a coding system similar to Brown et al . () and Yi and Lamb (). All information relating to people (e.g., a man), actions and affective states (e.g., broke), attributes (e.g., the blue), objects and settings (e.g., toy), and temporal information (e.g., afterwards) was given one point.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations